Analyzing The Stress Levels of A Patient Using Heart Beat and Pulse Rate Sensor by Arduino Interface with CRO - Arunamanjusha, K; Kalyani, T; Naresh, B; Nagaraju, N (International Journal of Engineering and Technology, 2018)
With the advancements in medical field, it is easy to treat numerous diseases and study various micro organisms and produce life saving drugs that did not exist few decades back. However, we do not have enough apparatus that is simple and user-friendly to analyze or make assessments to determine the psychological conditions of a patient. The treatment given to the patient is affected by the person’s psychological state of mind in terms of stress or emotional levels. A person’s stress levels are basically determined by the emotional response and in turn the electrical impulses generated through the exchange of sodium and potassium ions at the cell wall of the human body which is generally maintained at -70mV. The electrical impulses can be captured at the heart or brain or both in order to analyze the state of the patients receiving any particular treatment. In this paper the register pulse rate using heart beat sensor and graph it at certain intervals of time.  The slope joining the peaks of consecutive readings indicates the increase /decrease of the patients stress and responsiveness to the treatment